2019
DOI: 10.1177/1556264619844851
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Genetics and Genetic Testing Among Participants in the Jackson and Framingham Heart Studies

Abstract: Genetic analysis has become integral to many large cohort studies. However, little is known about longitudinal cohort study participants' attitudes toward genetics and genetic testing. We analyzed data from a survey of participants in the Jackson Heart Study (n = 960), Framingham Heart Study (n = 955), and Framingham Heart Study-Omni Cohort (n = 160). Based on a three-question attitude scale, most participants had positive attitudes toward genetic testing (median score = 4.3-5/5). Participants were also asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Studies have reported low levels of public understanding of genetic concepts such as the location of genes and applications such as newborn screening 1517. While other studies have investigated individuals’ attitudes toward genetic testing and their association with the interest in undergoing genetic testing 18,19. The individual’s attitudes toward genetic testing are important because of the efforts can be expended in establishing services that are accepted by the public and in concordance with people’s needs 20,21.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported low levels of public understanding of genetic concepts such as the location of genes and applications such as newborn screening 1517. While other studies have investigated individuals’ attitudes toward genetic testing and their association with the interest in undergoing genetic testing 18,19. The individual’s attitudes toward genetic testing are important because of the efforts can be expended in establishing services that are accepted by the public and in concordance with people’s needs 20,21.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey that included 560 women who had been offered prenatal screening in Ontario, the participants strongly supported the clinical utility of genetic testing in the diagnosis and management of diseases [18]. Similar positive attitude toward genetic testing was reported among Framingham Heart Study participants [19] and German population [20]. Thus, studies conduct worldwide showed positive attitude of people toward clinical uses of genetic testing to improve health-care services and prevention of diseases.…”
Section: Discussionmentioning
confidence: 63%
“…suggested that greater genetic literacy is associated with greater reported fear and uncertainty about the implications of genetic testing; and, in contrast, lack of understanding and unreasonable expectations may lead to unwarranted enthusiasm about testing and unrealistic hopes about its results [65,78]. Our data showed that, on average, participants correctly answered 60.4% of the genetic knowledge questions, which indicates insufficient knowledge given that the questionnaire tapped into basic knowledge regarding genetics.…”
Section: Plos Onementioning
confidence: 66%